Novel Atmospherically Plasma Sprayed Micro Porous Layer for Anion Exchange Membrane Water Electrolysis Operating With Supporting Electrolyte - Vincent Wilke; Marco Rivera; Tobias Morawietz; Noriko Sata; Lukas Mues; Manuel Hegelheimer; Artjom Maljusch; Patrick Borowski; Günter Schmid; Chen Yie Thum; Malte Klingenhof; Peter Strasser; et al. (Electrochemical Science Advances, 2025)
ABSTRACT Anion exchange membrane water electrolysis (AEMWE) is one of the most promising candidates for green hydrogen production needed for the de‐fossilization of the global economy. As AEMWE can operate at high efficiency without expensive Platinum Group Metal (PGM) catalysts or titanium cell components, required in state‐of‐the‐art proton exchange membrane electrolysis (PEMWE), AEMWE has the potential to become a cheaper alternative in large‐scale production of green hydrogen. In AEMWE, the porous transport layer and/or micro porous layer (PTL/MPL) has to balance several important tasks. It is responsible for managing transport of electrolyte and/or liquid water to the catalyst layers (CLs), transport of evolving gas bubbles away from the CLs and establishing thermal and electrical connection between the CLs and bipolar plates (BPPs). Furthermore, especially in case the CL is directly deposited onto the MPL, forming a catalyst‐coated substrate (CCS), the MPL surface properties significantly impact CL stability. Thus, the MPL is one of the key performance‐defining components in AEMWE. In this study, we employed the flexible and easily upscaled technique of atmospheric plasma spraying (APS) to deposit spherical nickel coated graphite directly on a low‐cost mesh PTL. Followed by oxidative carbon removal, a nickel‐based MPL with superior structural parameters compared to a state‐of‐art nickel felt MPL was produced. Due to a higher activity of the nickel APS‐MPL itself, as well as improved catalyst utilization, a reduction in cell voltage of 63 mV at 2 A cm−2 was achieved in an AEMWE operating with 1 M KOH electrolyte. This improvement was enabled by the high internal surface area and the unique pore structure of the APS‐MPL with a broad pore size distribution as well as the finely structured surface providing a large contacting area to the CLs.